The phenotype of adverse drug effects: Do emergency visits due to adverse drug reactions look different in older people? Results from the ADRED study - Just, Katja S.; Dormann, Harald; Schurig, Marlen; Böhme, Miriam; Steffens, Michael; Plank-Kiegele, Bettina; Ettrich, Kristin; Seufferlein, Thomas; Gräff, Ingo; Igel, Svitlana; Schricker, Severin; Jaeger, Simon U.; et al. (British Journal of Clinical Pharmacology, 2020)
Aims: Older patients in particular suffer from adverse drug reactions (ADR) when presenting in the emergency department. We aimed to characterise the phenotype of those ADRs, to be able to recognise an ADR in older patients. Methods: Cases of ADRs in emergency departments collected within the multicentre prospective observational study (ADRED) were analysed (n = 2215). We analysed ADR-associated diagnoses, symptoms and their risk profiles. We present frequencies and odds ratios (OR) with 95% confidence intervals for adults (18–64 years) compared to older adults (≥65 years; young–old 65–79, old–old ≥80 years) and regression coefficients (B) for each year of age. Results: Most prominent differences were seen for drug-associated confusion, dehydration, and bradycardia (OR 6.70 [1.59–28.27], B.054; OR 6.02 [2.41–15.03], B.081, and 4.82 [2.21–10.54], B.040), more likely seen in older adults. Bleedings were reported in all age groups, but gastrointestinal bleedings occurred with more than doubled chance in older adults (OR 2.46 [1.77–3.41], B.030), likewise did other bleedings such as haemorrhage from respiratory passages (OR 2.89 [1.37–6.11], B.036). Falls were more likely in older adults (OR 2.84 [1.77–4.53], B.030), while dizziness was frequent in both age groups. Conclusion: Our data point to differences in symptoms of ADRs between adults and older individuals, with dangerous drug-associated phenomena in the older adult such as bleedings or falls. Physicians should consider drug-associated origins of symptoms in older adults with an increased risk for serious health problems.
CRIS-Team Scopus Importer:2025-02-03
Keywords: adverse drug reaction; emergency departments; network analysis; older adults; symptoms